2016
DOI: 10.5125/jkaoms.2016.42.5.259
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic and postoperative neurosensory deficits of the inferior alveolar nerve in mandibular fracture: a prospective study

Abstract: ObjectivesWe evaluated and recorded post-traumatic and postoperative neurosensory deficits of the inferior alveolar nerve (IAN) in mandibular fracture in order to identify associated risk factors.Materials and MethodsThis was a prospective cohort study composed of 60 patients treated for mandibular fracture. The primary study variable was the change between the post-traumatic IAN neurosensory examination score and the score after fracture reduction. Risk factors were categorized as demographic, anatomic, fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 28 publications
2
18
1
1
Order By: Relevance
“…If only the inferior alveolar nerve-bearing area (body and angle fractures) is considered, the prevalence in our study was very high at 93.0%. This was similar to that given by Yadav et al 19 of 86.7%. According to the review by Thurmüller et al 4 , the post-traumatic, pre-treatment nerve injury considering only angle and body fractures ranged from 46% to 58.5%, but the same study reported overall postoperative IAND to be in the range of 0.4% to 91.3%, or between 76.1% and 91.3% when only nerve-bearing area were considered.…”
Section: Discussionsupporting
confidence: 93%
“…If only the inferior alveolar nerve-bearing area (body and angle fractures) is considered, the prevalence in our study was very high at 93.0%. This was similar to that given by Yadav et al 19 of 86.7%. According to the review by Thurmüller et al 4 , the post-traumatic, pre-treatment nerve injury considering only angle and body fractures ranged from 46% to 58.5%, but the same study reported overall postoperative IAND to be in the range of 0.4% to 91.3%, or between 76.1% and 91.3% when only nerve-bearing area were considered.…”
Section: Discussionsupporting
confidence: 93%
“…It is mainly associated with the inferior alveolar nerve, and it is more frequent in the mandibular ramus fractures than in the mandibular body fractures. Most nerve injuries are likely to recover if early appropriate treatment is applied but cannot be recovered if the damage by the fracture itself or by the wrong operation is irreversible [ 15 ]. An impacted third molar may cause nerve injury.…”
Section: Main Textmentioning
confidence: 99%
“…Similarly, in a study of 583 patients, age was related to risk of complication [56]. Other studies also show that post-operative risks rise in frequency with increasing age [16,[57][58][59][60]. In a study in which germectomy was performed on 300 teeth in patients aged 12-19 years, no lingual nerve injury occurred [61].…”
Section: Discussionmentioning
confidence: 88%